PENGARUH EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP HEMATOKRIT MENCIT (Mus musculus L.) SWISS WEBSTER - Fauziah, Nurul; Sumarmin, Ramadhan; Indriati, Gustina (Pendidikan Biologi, 2013)
ABSTRACT Garcia is a medicinal herbal that have many benefits, not only as fresh fruit but also be healing  various  diseases.  The garcia  rind have xanthones  which  maintain  and precipitate  the formation  of  erythrocytes.  However,  the  garcia  rind  have  not  optimal  utilization  yet.  This research to know the effect of the garcia rind extract to the male mice hematocrit. The research has done at June to August  2013 in the zoology  laboratory  of biology department  faculty of mathematics and natural science Padang State University. This research used Completely Randomized   Design  (CRD)  with  4  treatments   and  6  repetitions.   Treatment   given  orally (gavage) 0.2, 0.4, and 0.6 g garcia rind extract peel per 25 g body weight for 35 days. The data of hematocrit  values were analyzed by ANOVA and continued by DNMRT. The results show hematocrit  values were 0.2 g per 25 g body weight is highest (52.20 %), whereas mice given the garcia rind extract peel  at a dose of 0.4 g (51.01 % and 0.6 g (49,20 %) per 25g per 25 g body weight  is impaired  hematocrit  although  still within  the normal  range.  From the resu lts obtained  in this research  shows F count> F table significant  0.05. It conclude  that the garcia rind extract increase the hematocrit of mice.